2016
DOI: 10.1016/j.jnnfm.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic settling of particles in shear flows of shear-thinning fluids

Abstract: General rights This document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: Abstract Dynamic settling is the phenomenon whereby a relatively dense particle settles through a sheared flow of a non-Newtonian fluid at a speed that depends on the shear rate of the background flow. This means that due to the non-linear rheology, the settling velocity may vary spatially and temporally as the background shear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Settling of suspensions in viscoplastic fluids can be categorized as static settling or dynamic settling, depending on the background flow conditions (quiescent in the former). It is well known in the oil industry that background shear enhances settling [15] in shear-thinning fluids. For viscoplastic fluids, Merkak et al [16] and Ovarlez et al [17] demonstrated shearinduced settling in fluids regardless of the yield number, showing that particles settle as soon as the fluid yield stress is overcome by macroscopic shear.…”
Section: Introductionmentioning
confidence: 99%
“…Settling of suspensions in viscoplastic fluids can be categorized as static settling or dynamic settling, depending on the background flow conditions (quiescent in the former). It is well known in the oil industry that background shear enhances settling [15] in shear-thinning fluids. For viscoplastic fluids, Merkak et al [16] and Ovarlez et al [17] demonstrated shearinduced settling in fluids regardless of the yield number, showing that particles settle as soon as the fluid yield stress is overcome by macroscopic shear.…”
Section: Introductionmentioning
confidence: 99%